Post-extubation dysphagia incidence in critically ill patients: A systematic review and meta-analysis. Issue 1 (January 2021) - McIntyre, Melanie; Doeltgen, Sebastian; Dalton, Nathan; Koppa, Mayank; Chimunda, Timothy
Abstract: Background: Post-extubation dysphagia has been associated with adverse health outcomes. To assist service planning and process development for early identification, an understanding of the number of patients affected is required. However, significant variation exists in the reported incidence which ranges from 3% to 62%. Objectives: The objective of this study was to (i) conduct a meta-analysis on the incidence of dysphagia after endotracheal intubation in adult critically ill patients and (ii) describe the extent of heterogeneity within peer-reviewed articles and grey literature on the incidence of dysphagia after endotracheal intubation. Data sources: Databases CINAHL, Cochrane Library, Embase, MEDLINE, PubMed, SpeechBITE, and Google Scholar were systematically searched for studies published before October 2019. Review methods: Data extraction occurred in a double-blind manner for studies meeting the inclusion criteria. Risk of bias was determined using critical appraisal tools relevant to the individual study design. The overall quality of the synthesised results was described using the Grading of Recommendations Assessment, Development and Evaluation methodology. Raw data were transformed using Freeman–Tukey arcsine square root methodology. A random-effects model was utilised owing to heterogeneity between studies. Results: Of 3564 identified studies, 38 met the criteria for inclusion in the final review. A total of 5798 patient events were analysed, with 1957 dysphagic episodes identified. The combined weighted incidence of post-extubation dysphagia was 41% (95% confidence interval, 0.33–0.50). Of the patients with dysphagia, 36% aspirated silently (n = 155, 95% confidence interval, 0.22–0.50). Subgroup meta-regression analysis was unable to explain the heterogeneity across studies when accounting for the method of participant recruitment, method of dysphagia assessment, median duration of intubation, timing of dysphagia assessment, or patient population. Conclusion: Dysphagia after endotracheal intubation is common and occurs in 41% of critically ill adults. Given the prevalence of dysphagia and high rates of silent aspiration in this population, further prospective research should focus on systematic and sensitive early identification methods.